PERENCANAAN STRATEGIS LEMBAGA PENDIDIKAN (Studi Kasus Pembelajaran Mandiri Integratif di Pondok Pesantren Mahasiswa Al-Hikam Malang) - Mochamad Nurcholiq (STAI Ma'had Aly Al-Hikam Malang, 2023)
This study aims to describe a form of strategic planning that is implemented in Islamic Education Institutions with the application of Integrated Self Access Learning (AISAL). AISAL is a learning offer by utilizing information technology. A qualitative approach used in this study, while the type of research is a case study. The implementation of this research begins with understanding and analyzing phenomena which are finally paired with theory. Strategic planning is currently very much needed in order to strengthen the existence of educational institutions. Planning is done through formulation, implementation, and evaluation. Activities that intersect with strategic planning include; competitive advantage, strategists, vision and mission statements, external opportunities and threats, internal strengths and weaknesses, long-term goals, strategy, annual objectives, and policies. The management of educational institutions must begin with a comprehensive strategic plan. The impact of this strategic planning is that there will be educational institutions that have a relatively permanent advantage (quality). This is due to the analysis of all aspects of the organization that may become obstacles in the future